First Description of the Female of Myrmica ritae (Hymenoptera, Formicidae), With Some Notes on the ritae Group - Radchenko, A.G.; Elmes, G.W. (Вестник зоологии, 1999)
The first known female of Myrmica ritae Emery is described and compared with the other known females of the ritae complex (M. serica Wheeler, M. indica Weber and M. gigantea (Collingwood). It differs from all three species bystraight (not sinuous) longitudinal ragae on the head dorsum, a shorter head and by relatively longer propodeal spines. M. rigatoi Radchenko et Elmes is proposed to be excluded from ritae group. Some new localities are added to the distribution of M. gigantea and M. urbanii Radchenko et Elmes.